2020
DOI: 10.1016/j.cell.2020.09.033
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Infection Depends on Cellular Heparan Sulfate and ACE2

Abstract: Highlights d SARS-CoV-2 spike protein interacts with heparan sulfate and ACE2 through the RBD d Heparan sulfate promotes Spike-ACE2 interaction d SARS-CoV-2 infection is co-dependent on heparan sulfate and ACE2 d Heparin and non-anticoagulant derivatives block SARS-CoV-2 binding and infection

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

53
1,215
7
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 988 publications
(1,287 citation statements)
references
References 67 publications
53
1,215
7
12
Order By: Relevance
“…In addition, we also found that heparin could also significantly inhibited SARS-CoV-2 pseudovirus infection ( Fig. S2A-C ), indicating heparins potential for treatment of SARS-CoV-2 infection, and the heparan sulphate could be the potential co-receptor for SARS-CoV-2 infection 14 . These findings suggest that hLPCs and also hAFECs are permissive for SARS-CoV-2 pseudovirus and GX_P2V infection.…”
Section: Resultsmentioning
confidence: 69%
“…In addition, we also found that heparin could also significantly inhibited SARS-CoV-2 pseudovirus infection ( Fig. S2A-C ), indicating heparins potential for treatment of SARS-CoV-2 infection, and the heparan sulphate could be the potential co-receptor for SARS-CoV-2 infection 14 . These findings suggest that hLPCs and also hAFECs are permissive for SARS-CoV-2 pseudovirus and GX_P2V infection.…”
Section: Resultsmentioning
confidence: 69%
“…8,9,[38][39][40][41][42][43][44][45][46][47] Further, heparin has been shown to block SARS-CoV-2 viral spike protein binding in experimental studies. [48][49][50] We postulate that the combination of heparin's known antithrombotic and anti-inflammatory effects, 6,7 in addition to viral infectivity attenuation may, at least in part, explain the observed benefit associated with prophylactic anticoagulation.…”
Section: Comparison With Other Evidencementioning
confidence: 99%
“…Enzymatic cleavage of protein S at the level of S1/S2 domains supports fusion of viruses to cell membranes via the S2 subunit (Liu et al, 2020). SARS-CoV2 S-protein interacts with both the cellular HS and ACE2 through its RBD and can simultaneously engage heparin and ACE2 (Clausen et al, 2020). Positively charged amino acids in a subdomain of RBD are responsible for the binding of heparin/HS complex via an interaction site that appears independent on the site involved in ACE2 binding (Clausen et al, 2020).…”
Section: Midkine Heparan Sulfate and Extracellular Matrix: A Role Fmentioning
confidence: 99%
“…SARS-CoV2 S-protein interacts with both the cellular HS and ACE2 through its RBD and can simultaneously engage heparin and ACE2 (Clausen et al, 2020). Positively charged amino acids in a subdomain of RBD are responsible for the binding of heparin/HS complex via an interaction site that appears independent on the site involved in ACE2 binding (Clausen et al, 2020). SARS CoV2 protein S appears to bind HS cooperatively with ACE2 receptor on the cell surface (Clausen et al, 2020).…”
Section: Midkine Heparan Sulfate and Extracellular Matrix: A Role Fmentioning
confidence: 99%